Unlocking Gen Z Potential in Government Institutions: The Impact of Self-Efficacy and Job Satisfaction on Organizational Citizenship Behavior - Sholihah, Husna; Sofiah, Diah; Ramadhani, Hetti Sari (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
In 2024, Generation Z accounted for 8% of the total number of civil servants (ASN) in Indonesia, totaling 312,870 employees. Previous studies have indicated differences in work values between Generation Z and earlier generations. These differences may lead Generation Z employees to avoid engaging in Organizational Citizenship Behavior (OCB), even though OCB is a crucial indicator of organizational performance. This study aims to examine OCB among Generation Z civil servants, with self-efficacy as the predictor variable and job satisfaction as the mediating variable. The participants consisted of 302 Generation Z civil servants working in the provincial government of Region XYZ. A purposive sampling technique was used for participant selection. Data were collected using three instruments: an OCB scale, a self-efficacy scale, and a job satisfaction scale. Data were analyzed using the Partial Least Squares – Structural Equation Modeling (PLS-SEM) method. The results showed that both self-efficacy and job satisfaction had a positive and significant influence on OCB. All hypotheses in this study were supported. These findings highlight the important role of self-efficacy and job satisfaction in enhancing OCB among Generation Z civil servants.